Firm efficiency and Input market integration Trade versus FDI - Michele Imbruno (FIW - Research Centre International Economics, 2015)
This paper highlights the crucial role played by international access to intermediate inputs to explain firm-level performance, via two channels simultaneously: trade and FDI. We develop a simple theoretical model showing that trade integration of input market entails an efficiency improvement within firms able to import (gains from input switching) and an efficiency decline within other firms (losses from domestic input availability). At the same time, FDI integration of input market implies non-importers' efficiency enhancement (gains from input switching) and some ambiguous effects on importers' efficiency (due to additional losses from foreign input availability). Using firm-level data from the Chinese manufacturing sector over the period 2002-2006, we find some results coherent with our theoretical predictions.
Keywords: F12; F14; F23; 330; Heterogeneous firms; Trade liberalization; FDI; Intermediate inputs; Productivity